SOIL PROPERTIES AND TREE COMPOSITION IN A 27-YEAR OLD Acacia mangium Willd. PLANTATION ON ABANDONED MINING AREA AT PHANGNGA FORESTRY RESEARCH STATION - Jetsada Wongprom; Roongreang Poolsiri; Sapit Diloksumpun; Chatchai Ngernsaengsaruay (BIOTROPIA, 2020)
In order to validate the important role of Acacia mangium plantation in mining rehabilitation, a study was conducted on the soil properties and tree composition in a 27-year-old A. mangium plantation growing on sandy (S27) and clay (C27) soil types, as well as a mixed plantation (MP) growing on clay soil type. The results were compared with those grown on an abandoned mining area (AB), a secondary forest (SF) and a primary forest (PF), at the Phangnga Forestry Research Station, Thailand. Three 40 x 40 m permanent plots were established and soil samples were randomly collected from depths of 0-10, 10-20, 20-30, and 30-50 cm, in each of the S27, C27, MP, AB, SF, and PF. The bulk density values in the S27, C27, and MP were lower than that in AB and was similar to those in SF and PF, particularly, the top soil. Total nitrogen, available phosphorus, organic matter, exchangeable potassium, and magnesium contents in the S27, C27, and MP were higher than that in AB, but were lower than those in SF and PF, indicating that the soil development in the S27, C27, and MP was slower than in the SF and PF. This lower bulk density values and higher soil nutrient contents were positively contributed by the A. mangium plantation. The Shannon-Wiener index obtained for S27 (1.43), C27 (2.51), and MP (2.77) were lower than that for the SF (3.86). The similarity indices of the tree species found in S27, C27, MP, and PF were low, ranging from 5.83-8.00, indicating that the development of the forest community was slow compared to SF (31.03). Enrichment planting with poorly dispersed shade tolerant trees has increased the diversity and improved the forest structure in the mined out areas and other similarly degraded lands.